2003
DOI: 10.1002/jbm.b.10065
|View full text |Cite
|
Sign up to set email alerts
|

Premixed calcium–phosphate cement pastes

Abstract: A self-hardening calcium-phosphate cement (CPC) containing Ca(4)(PO(4))(2)O and CaHPO(4) has been shown in clinical studies to be efficacious for repairing bone defects. This and several other similar CPCs harden in 10 min with the use of a phosphate solution as the liquid and form hydroxyapatite (HA) as the product. The present study investigated the properties of water-free, glycerol-containing CPC pastes that are stable in the package and would harden only after being delivered to a defect site where glycer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(116 citation statements)
references
References 13 publications
3
110
0
3
Order By: Relevance
“…Hydroxypropyl methylcellulose (HMC) and Na2HPO4 (disodium hydrogen phosphate) was added to improve the paste cohesiveness and accelerate cement hardening, respectively. This premixed-CPC exhibited good handling properties, set in an aqueous environment, and formed hydroxyapatite as the final product 13) . The results of a preliminary in vivo study using a rabbit model showed that the material had good biocompatibility 14) .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hydroxypropyl methylcellulose (HMC) and Na2HPO4 (disodium hydrogen phosphate) was added to improve the paste cohesiveness and accelerate cement hardening, respectively. This premixed-CPC exhibited good handling properties, set in an aqueous environment, and formed hydroxyapatite as the final product 13) . The results of a preliminary in vivo study using a rabbit model showed that the material had good biocompatibility 14) .…”
Section: Introductionmentioning
confidence: 98%
“…Sugawara et al 12) reported that the glycerol-CPC paste showed better biocompatibility than a number of presently used root canal filling or sealing materials. Takagi et al 13) also reported the feasibility of formulating premixed-CPCs that are stable in a package, resist washout, and will harden only after being delivered to the defect site. Glycerol was used as the liquid because the CPC hardening reaction does not occur in a water-free glycerol environment.…”
Section: Introductionmentioning
confidence: 99%
“…La creación de macroporos en el cemento mediante la incorporación de ciertas sustancias hidrosolubles como el bicarbonato 42 . Finalmente, en los últimos años se han desarrollado algunos cementos premezclados que tienen la ventaja de no endurecerse hasta que se inyectan dentro del hueso, pero con la desventaja de que dicho endurecimiento es mucho más lento y su resistencia es menor 43 . (Tabla 1).…”
Section: Discussionunclassified
“…A minimal amount of manipulation required by the surgeon is therefore ideal, in order to ensure time-efficient, repeatable results. A pre-mixed material may thus be of interest [48].…”
Section: Handlingmentioning
confidence: 99%
“…Only in the case of premixed ceramic cements, where e.g. glycerol is added to obtain an injectable paste, one can obtain a longer working time, since in this case, the setting starts only once the material is inside the body [48]. PMMA based bone cements used in vertebroplasty should generally have a working time of 6-10 minutes and a setting time of approximately 15 minutes [45].…”
Section: Working and Setting Timesmentioning
confidence: 99%